FAKTOR PERCERAIAN DI MASA PENDEMI COVID-19 KASUS DI PA Nomor 1418/Pdt.G/2020/Pdt.Mdn - Harahap, Herlina Hanum; Ramadhan, Maulana (Jurnal Ilmiah METADATA, 2021)
Law No. 1 of 1974 provides an understanding of marriage. Article 1 states that marriage is an inner and outer bond between a man and a woman as husband and wife, with the aim of forming a happy and eternal family (household) based on God Almighty. The definition of divorce in general is the breaking of the marital relationship between husband and wife in marriage law caused by certain causes which according to both parties cannot be reunited in a sacred marriage bond. The problem of this research is what is the factor in divorce during the COVID-19 pandemic, decision number 1418/Pdt.G/2020/Pdt.Mdn, The method used in this study The approach method of this research uses an empirical juridical approach. The empirical juridical approach method is used to analyze the laws and regulations relating to marriage and divorce and there are legal principles. And also conduct field research directly to the Medan Religious Court. The conclusion of this study is that you have to be patient in dealing with the problems given by Allah SWT.